A política no Território Federal de Rondônia: tramas e artimanhas para a criação do estado de Rondônia - Silva, Walfredo Tadeu Vieira da (2024)
This paper addresses the process of deterritorialization from the lands of Rondônia during a recent colonization (1960-1985), demonstrating the changes coming in the Federal Territory of Rondônia (1956-1981), whether economical with the transfer of the connection to the industrial-manufacturer axis of the South-Center with the construction of the HWY 029/364 (BR-029/364). Also the expansion of agricultural projects and tin ore (cassiterite) extraction on the newly opened road section, either political, with the weakening of the old elites of the Ferreira family, connected to the rubber tapper and the shop owners of the capital of the State of Rondônia, Guajará Mirim, and the starting of the fortification of the laborism with the leveraging development by the PTB (Political Party), UDN and PSP in the territory called shortskin. This situation had been modified by the occurrence of the military coup d’Etat of 1964 and the institution number 2, which extinguished all political parties and imposed bipartisanship between the Military Dictatorship party called ARENA and a consented opposition called MDB and even the social changes because of the migratory flow from the South-Center. Considering that the urban colonization in Rondônia which was a directed rural colonization that did not serve the people attracted to the region called agriculture border, based on the mottos “landless men and land without men” and also “interact so as not to deliver”. That was boosted by the recent geopolitical military project, changing the political strength to the East and the SouthCenter region of the future State of Rondônia. This region concentrates an agricultural production and the agricultural industry removing the focus of the Madeira Mamoré region, fixed on HWY 029/364 (BR-029/364). The protagonist in the political and economic decisions. These socio-partial changes expand even more because of the territory transformation in the Federal State in 1981. This new scenario demonstrates the plots and tricks of the military dictatorship to direct in the name of the security and defense of the border since the creation of the Guaporé Federal Territory until the myth creator of the State Rondônia, Mr. Jorge Teixeira de Oliveira. He was the last governor of the State of Rondônia. These political tricks mean an impact over the lives of native populations, rubber tappers and indigenous – generating social and ethical conflicts, questioning the State’s propaganda by the Federal Government and the local elites, from the installation of the territory and later the State of Rondônia. This impact on the indigenous populations are neglected by the historiography marking socio-political-ethnic invisible, which favored the massacre of countless indigenous groups along the historical process of the Rondônia people.